Scientific «borrowing» - Kostrub, Oleksandr; Zazirniy, Igor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
The authors raise the issue of plagiarism in the orthopedic literature. This problem is typical for the world of science, but today there is a sharpening process.